2017
DOI: 10.1177/0956462417704344
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of adjunct universal rectal screening for Chlamydia genital infections in women attending Canadian sexually transmitted infection clinics

Abstract: Adding universal rectal screening to urogenital screening should positively impact rectal Chlamydia trachomatis (CT) incidence in affected populations. A dynamic Markov model was used to evaluate costs and outcomes of three rectal CT screening strategies among women attending sexually transmitted infection clinics in Alberta, Canada: universal urogenital-only screening (UG-only), additional selected (exposure-based) rectal screening (UG+SR), and additional universal rectal screening (UG+UR). The model included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This is because selective rectal testing policies result in many untested rectal infections that are coincidentally azithromycin-treated for vaginal CT [3, 6, 7]. Rectal testing is highly acceptable [4–6], and universal rectal testing has been found to be cost-effective in the STI clinic context [30]. Pooling of samples may contribute to reduced costs.…”
Section: Discussionmentioning
confidence: 99%
“…This is because selective rectal testing policies result in many untested rectal infections that are coincidentally azithromycin-treated for vaginal CT [3, 6, 7]. Rectal testing is highly acceptable [4–6], and universal rectal testing has been found to be cost-effective in the STI clinic context [30]. Pooling of samples may contribute to reduced costs.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were conducted on STD clinics ( 51 , 52 ), one in an abortion clinic ( 50 ), and another in multiple high-risk settings, including abortion clinics ( 49 ). These studies yielded quite different results as they used different comparators.…”
Section: Resultsmentioning
confidence: 99%
“…A study from the USA conducted in an STD clinic found that the self-obtained vaginal Aptima Combo 2 (AC2) strategy was the most cost-effective, savings $2384 per PID ( 51 ). Another Canadian STD clinic-based study found that adding rectal screening both universally and selectively to urogenital screening would be cost-effective if the CA$50,000 <WTP <CA$100,000 ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that a community-based intervention in Sweden called ‘Chlamydia Monday’—consisting of the provision of information and increased availability of testing, treatment and contact tracing—was cost-effective [ 59 ]. The last study focused on rectal chlamydia trachomatis screening as an add-on to female urogenital screening in STI clinics in Canada, and highlighted that selected and universal rectal screening are cost-effective compared to universal urogenital-only screening strategies [ 60 ].…”
Section: Methodsmentioning
confidence: 99%